Comparison of the Effect of Hip and Knee Strengthening with Internal Instruction Exercises on Pain and Dynamic Knee Valgus in Patients with Patellofemoral Pain Syndrome - Fatemeh Aghakeshizadeh; Amir Letafatkar (Vesnu Publications, 2020)
Introduction: Patellofemoral pain syndrome (PFPS) is one of the most common musculoskeletal disorders, and is related to biomechanical factors of the lower extremities. Hip and knee muscle strengthening is a well-known method for the treatment of PFPS, but there is insufficient evidence for its effectiveness in combination with other effective interventions. The purpose of this study was to compare the effect of hip and knee strengthening with internal instruction exercises on pain and dynamic knee valgus in patients with PFPS. Materials and Methods: The present study was a quasi-experimental intervention. 50 men and women with PFPS (18 to 45 years) participated in this study. Subjects were assigned to experimental (n = 25) and control (n = 25) groups. Evaluation of pain was conducted using visual analog scale (VAS) questionnaire, and dynamic knee valgus by two-dimensional video camera. Subjects in the control group received hip and knee strengthening exercises, and in the experimental group performed hip and knee strengthening with internal instruction exercise for six weeks, three sessions per week and each session for 45 minutes. Independent and dependent t tests were used for statistical analysis. Results: Adding internal focus instruction on hip and knee strengthening exercises affected the dynamic knee valgus angle of the patients with PFPS, and significantly reduced the dynamic knee valgus angle (P < 0.001). Moreover, there was no significant statistical effect on pain with the addition of internal focus on hip and knee strengthening exercises. Conclusion: Hip and knee strengthening with internal instructions exercises seem to be more effective in improving dynamic knee valgus than exercises that focus solely on strengthening the hip and knee muscles.